A DESCRIPTIVE STUDY ON THE PROFILE OF SOME POTENTIAL ENGLISH LANGUAGE TEACHERS - Ismail Hakki Mirici; Gonca Yangın Ekşi (Informascope, 2016)
This study aims to investigate why high school students might wish to choose teaching as a career. Who chooses teaching and why is important for policy makers the teacher is an important variable in determining the quality of education. Countries, especially developing ones, are aware that they need to train better teachers who would educate citizens of the 21st century. Teacher recruitment policies also play a role in the selection and maintenance of practicing teachers.  This study aims to (1) investigate the motives of high school students who wish to major in English, and most of whom may become English language teachers as a result of alternative recruitment policies; (2) to find out some information about the student's language learning beliefs and habits. The opinions of their parents and their language teachers have also been looked into to uncover any persuasion or dissuasion from people around the entrants. Three questionnaires were developed by the researchers to gather information from 86 students, 30 parents and 29 teachers. The data of the study were analyzed via frequency distributions and percentages to demonstrate the motives and profiles of students and the opinions and influence of parents and teachers. The findings suggest that students may choose teaching English as a career because they like it and they are interested in the language and its culture. Teaching is also regarded as an advantageous job by students and their parents. Language teachers persuade students who have some perceived ability to teach and who like languages. The findings show that because of the entrance exam used for selection, students may lack proficiency in skills that are not assessed.